REDUKSI LONG PERIOD MULTIPLE DENGAN MENGGUNAKAN METODE HIGH-RESOLUTION RADON DEMULTIPLE (RAMUR) PADA DATA SEISMIK DARAT 2D - Faradina A. P.; Udi Harmoko; Fazrin Oktafian (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Multiples often occur in marine seismic data, but actually, they also occur in the far offset section of land seismic in that multiple reduction in land seismic data using CDP gather resulted from conventional method can be applied to acquire omitted multiple model. There are many methods to reduce the appearance of long period multiples, yet to remove multiples from primary signals is challenging. Compared to other methods, high-resolution Radon demultiple (RAMUR) is a method which uses Radon transform to predict multiples using domain tau-p to model multiples. RAMUR processing has more advantages in identifying reflection events, both in primary signals and multiples, to produce good stack sections. In this research, CDP gather resulted from conventional method was used as input in multiple modeling. Besides, adaptive subtraction process also apply CDP gather as input data to be subtracted with multiple model to preserve the data. The result shows that high-resolution Radon demultiple (RAMUR) method is able to reduce long period multiples in far offset section using DTCUT 120 parameter in land seismic effectively.